Kajian Dialegtologi Bahasa Serawai Perbandingan Antara Dialeg “Au” dan “O” di Kecamatan Air Nipis Kabupaten Bengkulu Selatan - Aprianty, Nadila Putri; Satria, Irwan; Sari, Wenny Aulia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This study aims to analyze and compare the "AU" and "O" dialects of Serawai language used in Sukarami and Maras villages, Air Nipis District, South Bengkulu Regency. The method used is a qualitative descriptive approach with dialectological methods, where data is collected through observation, interviews, and documentation, and then analyzed using inductive techniques, data reduction, data presentation, and conclusion drawing. The results show that there are significant differences between the "AU" and "O" dialects of Serawai, both in phonological and morphological aspects. In the phonological aspect, differences are found in the use of vowels, consonants, diphthongs, and sound changes, while in the morphological aspect, differences are found in affixation, reduplication, and compounding processes. The factors influencing these dialectal differences include geographic, social, and cultural factors of the local community. Furthermore, this study also reveals that the Serawai "O" and "AU" dialects diverged from the proto-language unit about 1,027±104 years ago, between 995-891 BCE. In conclusion, the differences between the "AU" and "O" dialects of Serawai in these two villages are influenced by various factors, including geographic, social, and cultural factors, and they have a linguistic development history that can be traced further through dialectological studies. Keywords: Serawai Language, Dialectology, Dialect "AU", Dialect "O"